Influence Human Resources Quality, Competence and Leadership on Employee Performance at the Department of Communication and Information North Sumatra Province - Luahambowo, Mil Adeven; Rostina , Cut Fitri; Barus, Hafiz Al Assad; Fauzi, Fauzi (Lembaga Riset Ilmiah, 2024)
This study aims to examine the effects of Human Resource Quality, Competence, and Leadership on Employee Performance at the Department of Communication and Informatics of North Sumatra Province. The research utilizes SPSS software to analyze data from the sample obtained at the research site. The study population consists of 30 employees at the Department of Communication and Informatics of North Sumatra Province. The research employs a quantitative approach. The findings reveal that Human Resource Quality, Competence, and Leadership have a positive and significant partial impact on Employee Performance at the Department of Communication and Informatics of North Sumatra Province. Additionally, the variables of Human Resource Quality, Competence, and Leadership have a significant simultaneous effect on Employee Performance at the Department. The coefficient indicates that 71.3% of Employee Performance can be explained by the relationship between Human Resource Quality, Competence, and Leadership.